A15 A case study framework for design and evaluation of a national project to improve prehospital care of myocardial infarction and stroke. Issue 11 (14th October 2011) - Essam, N; Davy, Z; Shaw, D; Spaight, A; Siriwardena, A N
Abstract : Background: Cardiovascular disease (CVD) affects 1.8% of the population annually, 0.9% with stroke and 0.8% with coronary heart disease. People suffering from CVD often present acutely to ambulance services with symptoms of acute myocardial infarction or stroke. Early and effective treatment prevents death, improves long term health and reduces future disability. Objective: Our aim is to develop a rational approach for informing the design and evaluation of a national project for improving prehospital care of myocardial infarction and stroke: the Ambulance Services Cardiovascular Quality Initiative (ASCQI), the first national improvement project for prehospital care. Methods: We will use a case study methodology initially utilising an evaluation logic model to define inputs (in terms of resources for planning, implementation and evaluation), outputs (in terms of intended changes in healthcare processes) and longer-term outcomes (in terms of health and wider benefits or harms), whether intended or incidental and in the short, medium or long term. Results: We will present an evaluation logic model for the project. This will be expanded to show the analytical techniques which we will use to explain how and why the project achieves its outcomes. This includes times series analyses, pattern matching, cross case syntheses and explanation building to inform an explanatory logic model. We will discuss how this model will be useful in determining the data that will need to be collected during the course of the project to inform the detailed explanation of how and why the project delivered its outcomes. Conclusion: The case study approach will enable us to evaluate the impact of this collaborative project in constituent ambulance services as well as the initiative as a whole. It will enable us to show whether and to what extent the project has had an impact, but also how and why this has happened.